Numerical Solutions of System of Second Order Boundary Value Problems using Galerkin Method - Rupa, Mahua Jahan; Islam, Md Shafiqul (GANIT: Journal of Bangladesh Mathematical Society, 2018)
In this paper we derive the formulation of one dimensional linear and nonlinear system of second order boundary value problems (BVPs) for the pair of functions using Galerkin weighted residual method. Here we use Bernstein and Legendre polynomials as basis functions. The proposed method is tested on several examples and reasonable accuracy is found. Finally, the approximate solutions are compared with the exact solutions and also with the solutions of the existing methods. GANIT J. Bangladesh Math. Soc.Vol. 37 (2017) 161-174